KARAKTERISTIK USAHA KECIL MENENGAH DAN PENERAPAN SISTEM INFORMASI AKUNTANSI SERTA SISTEM PENGENDALIAN INTERNAL UKM DI JAKARTA TIMUR - Weli Weli (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2019)
The purpose of this study is to analyze the practice of accounting information system and internal control by Small Business in Indonesia. The Small businesses in Indonesia still face various problems, especially about funding. This funding issue arises because of the limitations of small businesses in the infrastructure of accounting records. There is no support to access funding from the Bank. Considering there are several levels of small businesses, it is also interesting to examine how the characteristics of small businesses are related to the extent of the application of accounting information systems, and the implementation of internal control. Data were collected through surveys using questionnaires distributed to small businesses in East Jakarta. The results of data analysis support previous research that small business has not apply the information system of accounting widely, scores obtained by most small business low both for accounting information system and internal control system.